Penerapan Media Mind Mapping untuk Meningkatkan Hasil Belajar IPAS Kelas IV SD Muhammadiyah Sidoharjo Lamongan - Mabruroh, Naily Al; Dewantari, Sabbihisma Maydita; Hikmah, Musayyadatul; Aziz, Aftar Falah; I. U. K., Linaria Arofatul (ALSYS, 2023)
For an educator, the selection of a learning model should be done carefully so that the choice is appropriate or relevant to various other aspects of learning, is efficient and interesting. The low learning outcomes of students can be caused by a lack of supporting aspects that can attract students' interest in learning. This problem is often encountered in learning with many concepts, thus increasing student activity, one of which is learning Natural and Social Sciences (IPAS). The purpose of this study is to describe the increase in student learning outcomes after using Mind Mapping learning media. The purpose of this study is to explain the increase in student learning outcomes after using Mind Mapping learning media. This study applied the classroom action research method (PTK), which consisted of two cycles and four stages, namely planning, implementing, observing and reflecting. This study uses qualitative and quantitative data collection techniques. Student learning outcomes have increased after the application of this Mind Mapping learning media, from cycle I by 40% and cycle II by 80%. These results prove that the application of mind mapping media can improve the learning outcomes of fourth grade elementary school students.